Value of the Axial-Vector Coupling Strength in β and ββ Decays: A Review - Suhonen, Jouni T. (Frontiers in Physics, 2017)
In this review the quenching of the weak axial-vector coupling constant, g_A, is discussed in nuclear β and double-β decays. On one hand, the nuclear-medium and nuclear many-body effects are separated, and on the other hand the quenching is discussed from the points of view of different many-body methods and different β-decay and double-β-decay processes. Both the historical background and the present status are reviewed and contrasted against each other. The theoretical considerations are tied to performed and planned measurements, and possible new measurements are urged, whenever relevant and doable. Relation of the quenching problem to the measurements of charge-exchange reactions and muon-capture rates is pointed out.